"Sun and Shadow:" Exploring Marcel Breuer's Basic Design Principle. Issue 2 (3rd April 2021) - Tsilika, Evangelia
Abstract: This study is an exploration of Marcel Breuer's basic design methodology as it appears in his writings, particularly his 1956 monograph Marcel Breuer: Sun and Shadow, the Philosophy of an Architect . By identifying the influences that helped shape the background to his theoretical approach, and with the support of broader philosophical resources, the characteristics and subtleties of Breuer's particular concept of dualism in architecture are outlined. This allows for a new interpretative approach to the critical analysis of his postwar architecture, using structuralism, through which the specific qualities of Breuer's dualism are evaluated in terms of design.